Determinants of bank savings deposits in Peru: A region approach - Leyva Pedraza, Tatiana Angélica (2020)
The objective of this research was to identify the variables that determine the level of savings deposits in the banking system in the regions of Peru, because savings are used for investment and investment favors growth. For this, econometric regressions of bank savings were used with respect to the Gross Domestic Product per capita, the inflation rate, bank credit, the educational level of the population, and internet access. We worked with panel data corresponding to the 24 regions of Peru in the period 2010-2019 under the fixed effects model and the random effects model. The random effects model was chosen as the best using the Hausman test. The results showed that the level of departmental bank savings is determined, in a positive sense, by the Gross Domestic Product per capita, the inflation rate, bank credit, the average level of education of the population and the percentage of households that have access to internet services. In turn, the unit root test applied to residuals indicates that departmental bank savings are cointegrated in the long term with these variables identified as their conditioning factors.